Lean management implementation in Malaysian public sectors: Critical success factors and performance implications - Zarifa Amira, Zulkeflee; Gusman, Nawanir; Airin, Abdul Ghani (Sciendo, 2023)
This study aims to investigate the effects of lean management implementation on public sector performance along with the critical success factors of its implementation. The cross-sectional quantitative survey collected 131 responses from public organisations in Malaysia selected through a stratified random sampling procedure. Data were analysed using the structural equation modelling (SEM) approach with SmartPLS 4 professional. Lean resources, lean culture, and lean knowledge management are critical success factors for implementing lean management in the Malaysian public sector. Subsequently, the holistic implementation of lean management will enhance their performance. This study provides a practical viewpoint for practitioners to understand and validate the potential benefits lean management can sustain if implemented with the critical success factors. As a result, practitioners and policymakers could use the insight from this study to tailor strategies for leveraging public sectors' performance in Malaysia.